"That was a tip from my physician"—Gender‐specific pathways of patients and relatives to outpatient psychosocial cancer counselling centres—A qualitative study. Issue 6 (9th February 2022) - Billaudelle, Fabian; Bayer, Oliver; Hechtner, Marlene; Taylor, Katherine; Lang, Jennifer; Alt, Jürgen; Fried, Marius; Singer, Susanne
Abstract: Objective: This study aims to identify pathways patients and their relatives take to outpatient psychosocial cancer counselling centres. We had a special interest in how access for men can be eased. Methods: Cancer patients and relatives were purposively sampled in two regions in Germany. Participants were either outpatient cancer counselling centres (OCCCs) users or non‐users and participated in qualitative face‐to‐face interviews. We used different guidelines for users and non‐users. The interviews were analysed using content analysis. Results: One hundred and three people participated in the study. Important pathways to outpatient psychosocial cancer counselling centres for both men and women were: information about the service and its content, easy access (obtaining appointments quickly and without bureaucracy, close to home), and recommendations from another person, in particular from their treating physician. Pathways especially important for men are positive and repeated recommendations from their treating physician and other people they trust, organisation by others on the men's behalf, the Internet, the possibility to talk to a male counsellor, making it a routine in the hospital to refer distressed patients to the counselling services, and the emphasis on information sharing. Women reported more often than men that they discovered and accessed OCCCs via information material. Conclusions: Men in particular need recommendations from others, especially from their treating physician, in order to make use of psychosocial cancer counselling. In addition, stressing the provision of information instead of exploring and expressing emotions can ease access for men to cancer counselling. Key points: Psychosocial services aiming to ease access for men should create gender‐specific information material (flyers, websites, etc.) This information should especially highlight social and social‐legal advice Referrers, usually general practitioners or oncologists, should be made aware that their recommendation plays a crucial role in male cancer patients' and their relatives' access to outpatient psychosocial cancer counselling